Individual responses to a single oral dose of albendazole indicate reduced efficacy against soil-transmitted helminths in an area with high drug pressure - Walker, Martin (2021)
Department of Pathobiology and Population Sciences. Royal Veterinary College. Hatfield, United Kingdom/London Centre for Neglected Tropical Disease Research. Imperial College London. London, United Kingdom.